(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Open Shortest Path First (OSPF) is a widely deployed link-state Interior Gateway Protocol (IGP) designed for routing IP packets within a single Autonomous System (AS). This report details the methodology of implementing OSPF, highlighting its mechanism of building a topological map of the network and using Dijkstra’s Shortest Path First (SPF) algorithm to calculate optimal routes. Key aspects such as LSA flooding, neighbor adjacency formation, and multi-area design are examined. Results indicate OSPF provides fast convergence, efficient path determination, and loop-free topology, making it ideal for large enterprise networks.